Temporal variation of "solar dimming" induced by composite and carbonaceous aerosols: Observations from mineral‐rich eastern Indian region. Issue 10 (28th May 2014) - Latha, R.; Murthy, B. S.; Lipi, K.; Kumar, Manoj; Das, S. K.; Mahanti, N. C.
Abstract Composite and carbonaceous aerosol radiative forcing (RF) over Ranchi (23.5°N, 85.3°E) in eastern India at monthly and seasonal scales during February 2011 to January 2012 is derived from mean optical properties obtained from Sun‐sky radiometer and a radiative transfer model. Ranchi is located on the Chotanagpur plateau at 650 m above mean sea level; the region is unique with dense open active mines, a source of mineral aerosols with opposing optical properties such as coal and limestone. Diurnal mean composite aerosol RF at the surface, in the spectral band 0.3–3.0 µm increases from winter (December, January, February) to premonsoon (March, April, May) with maximum (−65 Wm−2) aerosol RF in March that is associated with highest black carbon (BC) aerosol optical depth (AOD), 0.05. Minimum surface aerosol RF occurs in July with minimum values of AOD and AODBC. Aerosol RF at top of the atmosphere is maximum (−17 Wm−2) in April, and is positive (+1.2 Wm−2) in March. On an average, carbonaceous aerosols (BC) contribute 8.8% to total AOD and about 60% to total atmospheric absorption. A rapid increase of BC is seen in the postmonsoon with 1.0 µg m−3 in September to 3.0 µg m−3 in October. Aerosol‐induced solar dimming is about 9.4% (premonsoon), 7.0% (monsoon), 10.6% (postmonsoon), and 10.2% (winter) of the surface radiation. Seasonal mean aerosol heating rate is observed to be maximum in premonsoon ( 1.15°K/d−1), followed by postmonsoon, while winter and monsoon experience minimum ( 0.45°K/d−1) heating, assuming typical aerosol profiles of the model.